Application of Hydrothermally Modified Sweet Potato Starch as a Substitute Additive for Soup Mixture. (25th August 2014) - Senanayake, S. A.; Ranaweera, K. K. D. S.; Gunaratne, A.; Bamunuarachchi, A.
Abstract : Potential application of modified sweet potato starch as a substitute thickener for corn starch was studied, by using native starches extracted from five different cultivars of sweet potatoes commonly available in Sri Lanka. Physicochemical properties (swelling power, water solubility index, pasting, and gelatinization) and digestibility of native and modified (heat-moisture treated, 20% moisture, 85°C for 6 hrs) starches were analysed. Modified Swp3 (Wariyapola white), Swp4 (Pallepola), and Swp5 (Malaysian) starches were selected based on the favourable conditions shown in the required physical and chemical properties and applied in a vegetable soup formula as a thickening aid. Corn starch added samples were kept as controls and the viscosity difference and sensory attributes were tested. Viscosity of the reconstituted soup powder and sensory analysis showed that Swp4 and Swp5 had significantly high level (P < 0.05 ) of sensory quality and the average rank for mouth feel (taste), texture and overall acceptability was significantly high (P < 0.05 ) in Swp5 added samples. Shelf life studies ensured 6 months of stability with negligible level of moisture increase and total plate count in air tight polypropylene packages at ambient temperatures (28–31°C). Results of this study revealed a possibility of applying physically modified Swp4 and Swp5 starches as a substituent food ingredient for commercially available corn starch to improve the thickness of food products.